xy - 2x + y = 3
=> x ( y - 2) + ( y - 2 ) = 3 - 2
=> ( x + 1 ) ( y - 2 ) = 1
=> x + 1 và y - 2 thuộc Ư(1) = { 1; -1 }
Lập bảng:
x + 1 | 1 | -1 |
x | 0 | -2 |
y - 2 | -1 | 1 |
y | 1 | 3 |
Vậy x=0 , y=-2 hoặc x=1 , y=3
\(\text{xy - 2x + y = 3}\)
\(\text{\Rightarrow x ( y - 2) + ( y - 2 ) = 3 - 2}\)
\(\text{\Rightarrow( x + 1 ) ( y - 2 ) = 1}\)
=> \(\text{x + 1}\) và \(\text{y - 2}\) thuộc \(Ư_{\left(1\right)}\in\left\{\pm1\right\}\)
Lập bảng:
\(x+1\) | \(1\) | \(-1\) |
\(x\) | \(0\) | \(-2\) |
\(y-2\) | \(-1\) | \(1\) |
\(y\) | \(1\) | \(3\) |
Vậy \(\left(x;y\right)\in\left\{\left(0;-2\right);\left(1;3\right)\right\}\)
a) Ta có: xy - 2x +y = 3
x( y-2) +( y-2)= 3-2
(x+1)(y-2)=1=1.1= -1.(-1)
Ta có bảng sau
x+1 | 1 | -1 |
y-2 | 1 | -1 |
x | 0 | -2 |
y | 3 | 1 |